Relationship between Sedentary Lifestyle and Obesity in Elementary School Age Children at Lentera Harapan Elementary School Tomohon - Yofania Cicilia Saragih; Theo W.E. Mautang; Vera Diane Tombokan (Jurnal EduHealth, 2025)
The purpose of this study was to determine the relationship between sedentary lifestyle and obesity in children aged 9-12 years at SD Lentera Harapan Tomohon. Quantitative research method with cross sectional study design. The population amounted to 116 people using total sampling. Research results: children who do low-level sedentary lifestyle as many as 43 respondents (37.1%), respondents with moderate-level sedentary lifestyle as many as 28 respondents (24.1%), and children with high-level sedentary lifestyle 45 respondents (38.8%) where school-age children dominate in doing high-level sedentary lifestyle, which is one of the factors for obesity in children. Children with obesity and non-obese status also carry out low to high levels of sedentary lifestyle, which is one of the factors for obesity in school-age children with a percentage of 42 children (36.2%) and those who are not obese are 74 children (63.8%). The analysis test shows that the p value = 0.000 (<0.05) means that there is a significant relationship between sedentary lifestyle and obesity in children aged 9-12 years at SD Lentera Harapan Tomohon.